POD-based ROM applied to unsteady free surface water flow - Solán Fustero, Pablo; Gracia, José Luis; Navas-Montilla, Adrián; García-Navarro, Pilar (Jornada de Jóvenes Investigadores del I3A, 2023)
The numerical resolution of shallow water equations (SWE) is required in many environmental problems involving free surface flows. The upwind augmented Roe’s method [2] is widely used due to the robust and stable solutions it offers in realistic scenarios if properly corrected to deal with entropy fix and wet–dry fronts. On the other hand, reduced-order models (ROMs) are known to achieve more efficiency in terms of computational cost without losing accuracy. In this work, we analyse the properties and performance of a proper orthogonal decomposition (POD) based ROMs for this type of flows.